Turning Donepezil into a Multi-Target-Directed Ligand through a Merging Strategy - Perone, Rosaria; Albertini, Claudia; Uliassi, Elisa; Di Pietri, Flaminia; de Sena Murteira Pinheiro, Pedro; Petralla, Sabrina; Rizzardi, Nicola; Fato, Romana; Pulkrabkova, Lenka; Soukup, Ondrej; Tramarin, Anna; Bartolini, Manuela; et al. (ChemMedChem, 2021)
Thanks to the widespread use and safety profile of donepezil (1) in the treatment of Alzheimer's disease (AD), one of the most widely adopted multi-target-directed ligand (MTDL) design strategies is to modify its molecular structure by linking a second fragment carrying an additional AD-relevant biological property. Herein, supported by a proposed combination therapy of 1 and the quinone drug idebenone, we rationally designed novel 1-based MTDLs targeting Aβ and oxidative pathways. By exploiting a bioisosteric replacement of the indanone core of 1 with a 1,4-naphthoquinone, we ended up with a series of highly merged derivatives, in principle devoid of the "physicochemical challenge" typical of large hybrid-based MTDLs. A preliminary investigation of their multi-target profile identified 9, which showed a potent and selective butyrylcholinesterase inhibitory activity, together with antioxidant and antiaggregating properties. In addition, it displayed a promising drug-like profile.
Keywords: Acetylcholinesterase; Antioxidants; oxidační stres; Amyloid beta-Peptides; Cell Line, Tumor; drug design; Protein Aggregates; Oxidative Stress; Structure-Activity Relationship; lidé; amyloidní beta-protein; Blood-Brain Barrier; hematoencefalická bariéra; donepezil; Donepezil; Ligands; Humans; Alzheimer's disease; proteinové agregáty; Indans; acetylcholinesterasa; racionální návrh léčiv; Neuroprotective Agents; Alzheimer Disease; multi-target drug discovery; antioxidancia; medicinal chemistry; Drug Design; vztahy mezi strukturou a aktivitou; Alzheimerova nemoc; Cell Survival; polypharmacology; ligandy; viabilita buněk; cholinesterasové inhibitory; Cholinesterase Inhibitors; indany; nádorové buněčné linie; neuroprotektivní látky